Uppsala Latvian Library and Its Donation to Latvia in 1989 - Dreimane, Jana (Knygotyra, 2020)
In the USSR-reoccupied Latvia (1944−1990), almost all the Latvian literature, published abroad after World War II, was forbidden to the general public. There were only two incomplete and restricted collections of emigration literature, available to prominent scientists and highest Soviet officials. As the Soviet censorship weakened in the late 1980s, libraries could begin start a systematic acquisition of exile books and some periodicals. The donation of the whole library of the Uppsala Latvian society to the State Library of Latvia (now the National Library of Latvia) in 1989, before the renewal of Latvia’s independence, started the flow of emigration books, documents, and artefacts to the memory institutions of Latvia, where the most important cultural heritage from the Latvian exile has found its home. Using the documents of the Uppsala Latvian Society kept at the National Archives of Latvia, the National Library of Latvia, and the Academic Library of the University of Latvia, the history of the library and the importance of its donation in the accumulation of exile cultural heritage in Latvia has been characterized.The study shows that despite the library manager’s efforts to provide readers with the best emigrant Latvian literature, the library collection in exile was not properly valued − its readership gradually decreased as Latvians became more and more integrated into Swedish society. After the transfer to Latvia, the library became the basis of the of the unified collection of Latvian literature, in which exile publications are constantly utilised as an important part of the national cultural heritage.
Keywords: Soviet censorship; Latvian exile libraries; Uppsala Latvian society; collection of Latvian national literature; National Library of Latvia